Application of the SAW Method in a Decision Support System to Determine the Best Public Transportation Mode for UPN “Veteran” Jakarta Students - Nareswari, Fausta Sarah; Ramadhan, Rafa Muhammad Ghifar; Al-Ghifari, Muhammad Hanif; Niqotaini, Zatin (Universitas Amikom Yogyakarta, 2025)
Purpose: The high use of private vehicles in Jakarta exacerbates traffic congestion, making public transportation a vital alternative, especially for students of the National Development University